PERENCANAAN FASILITAS PERAIRAN PELABUHAN PENYEBERANGAN JUATA LAUT TARAKAN BERDASARKAN ANALISIS KEDALAMAN DAN KEBUTUHAN - Muh Yusril Syam; Muhammad Arsyad; Ainun Chandra Puspa Ningrum (Politeknik Negeri Batam, 2026)
Water transport in Tarakan plays an important role in passenger mobility and goods distribution. However, port operations still face limitations related to water depth and supporting infrastructure. This study aims to analyse the requirements and plan the water-based facilities of Juata Laut Ferry Port using an adaptive approach based on existing site conditions. The methodology includes tidal analysis using the least squares method, wave analysis based on ECMWF data, wind analysis with Windrose, and bathymetric evaluation in accordance with the Directorate General of Water Transport (2014) guidelines. The results show that wave conditions (SWH ≤ 0.77 m) and wind conditions are generally low to moderate, posing no significant operational constraints. Bathymetric analysis, however, identifies shallow areas (<5 m) that may interfere with navigation, particularly during low tide. Technical calculations indicate that the required waterway facilities comply with regulatory standards but need adjustment to local hydrographic conditions. Therefore, port facility planning should adopt a site-specific and adaptive approach by utilising natural depth corridors and limited dredging in critical areas to improve navigational safety, operational efficiency, and long-term sustainability.